Reimagining Gender in Webtoon – Queer Utopianism in H-P Lehkonen's Immortal Nerd and Its Reader-Response - Romu, Leena (Routledge, 2025)
According to utopian studies, utopias can work as transformative tools that expand our understanding of the possible. Using a thematic analysis of the reader-responses of a queer and utopian webcomic, H-P Lehkonen’s Immortal Nerd (2015–2017), the chapter asks how readers use the comic’s visual-verbal information to interpret, negotiate and imagine a future that is beyond today’s heteronormative gender binary. The analysis shows that readers are attentive to visual and verbal cues for representing gender and eagerly express their observations, ideas, and assumptions in the comment section where meanings about gender are then socially negotiated. Topics discussed by the readers included gendered beauty norms, conception of gender, nonbinary people, gender-neutral pronouns, and values such as acceptance, respect, diversity, and open-mindedness – topics that are essential for contemporary feminisms. The social aspect of Webtoon enables the readers to learn not only from the comic itself but also from each other which, the chapter argues, makes Webtoon a possible platform for online micro activism, a method of opinion changing that consists of small, everyday activities and interventions.
Comics, Activism, Feminisms